Association between olfactory function and quality of life in patients with olfactory disorders: a multicenter study in over 760 participants - Zou, Lai-quan; Hummel, Thomas; Otte, Martin S.; Bitter, Thomas; Besser, Gerold; Müller, Christian A.; Welge-Lüssen, Antje; Bulut, Cem; Göktas, Önder; Negoias, imona.; Li, Shu-Bin; Haehner, Antje (Rhinology, 2021)
This cross-sectional, multi-centric study aimed to investigate the differences in quality of life among patients with olfactory dysfunction (OD) of different origin, and to identify factors associated with olfactory-related quality of life (QOL)
Gesehen am 28.09.2022